3D QSAR and docking studies on benzoylsulfonohydrazides as histone acetyltransferase KAT6A inhibitors - MD. Muzaffar-Ur-Rehman, Syed Akbar, Asra Ali Bahazeq (Journal of Applied Pharmaceutical Science, 2020)
Sixty-one analogs of benzoylsulfonohydrazides were subjected to 3D QSAR studies using CoMFA and CoMSIA techniques followed by docking studies to develop a correlation of the structure with their respective activities. The generated model had shown good predictability and the contour analysis followed by docking study has provided an insight to develop new inhibitors. The cross-validation values corresponding to CoMFA and COMSIA were observed to be within the acceptable criterion (q2 > 0.5). The docking analysis of the best active compound shown was −11.81 kcal/mol. From the obtained analysis results of CoMFA as well as CoMSIA, the data can be useful to develop more potent histone acetyltransferase inhibitors.
Keywords: 3D QSAR, CoMFA, CoMSIA, docking, benzoylsulfonohydrazides, HAT.